APLIKASI MULTIMEDIA INTERAKTIF PEMBELAJARAN MEMBACA, MENULIS, BERHITUNG (CALISTUNG) - Adam Faroqi; Barikly Maula (JURNAL ISTEK, 2014)
The future of information technology will involve a lots of using advance information technology and high speeds of communication technology within global network. With the basic of multimedia technology and supporting by advance high speeds computer system, the service information system may be published into more interest and real form within multimedia information form, also easy to manage and use for personal computer. Method of Development of peripheral of application multimedia use the Luther (Sutopo, 2003) method that is process used to assist the software developer in forming model from software which must be made. In this application making, using force in the form of aid of application of processor media draw the, animation, and also authoring consisted of by the Adobe photoshop, Adobe Director, Adobe Flash, and processor application voice the Sony Vegas. Interactive learner multimedia which helped by computer can help students to learn and understand how to read, write, and calculate. One of those interactive multimedia has been made to helps children in learning read, write, and calculate. Those multimedia program made by compound some animation, picture, film, and games which connected to material for reading, writing, and calculating. The virtual picture is used for children to understand and learn from the material by comparing with a real things in our life. This interactive learner multimedia was packed in compact disc form, which can operated with computer. Those interactive multimedia program built for children in PAUD grade especially in TK Kencana Sukabumi. With existing of this application hoped can give plus point for child and also for the other media in learner.